Analysis of the Usability Level of the JKN Mobile Application Using the User Experience Questionnaire (UEQ) and Importance–Performance Analysis (IPA) Methods - Haris, Gendhi; Tri Julianto, Indri; Ridwan Ibrahim, Maulana (Journal of Applied Information System and Informatic (JAISI), 2025)
The JKN Mobile application developed by BPJS Kesehatan is a digital service for National Health Insurance (JKN) participants to access features for checking membership, online queues, and complaint services. JKN Mobile contributes significantly to the digitalization of healthcare services, but various negative reviews still emerge, especially regarding the interface aspect. This study analyzes the usability level of the application using the User Experience Questionnaire (UEQ) and Importance Performance Analysis (IPA) methods. The UEQ assesses six aspects of user experience, while IPA maps attributes based on importance and performance. The analysis results show a gap between expectations and experience. Clarity (1.1056, 0.4021), efficiency (1.0181, 0.0026), and appeal (1.0946, -0.019) fall into the "maintain performance" quadrant. Novelty (0.0965, 0.4113) is in the "top priority" quadrant, stimulation (0.8763, -0.1192) is a low priority, while accuracy (0.9514, -0.1224) is excessive. These findings provide a comprehensive overview of aspects that need to be maintained or improved. User feedback-driven strategies and agile approaches are recommended to make application development more innovative, optimal, and responsive to the needs of digital healthcare services.